Peningkatan Kapasitas Ekonomi Rumah Tangga Miskin Perkotaan Melalui Edukasi Kewirausahaan Sosial - Ayu, Ade Rahma (Sekolah Tinggi Ilmu Manajemen Sukma Medan, 2025)
Urban poverty in Medan is characterized by limited access to education and formal economic opportunities. This community service program aims to empower poor households in Patumbak Village, Medan Amplas District, through structured social entrepreneurship education. The implementation method utilized the Participatory Technology Development (PTD) approach, which includes partner identification, problem mapping, participatory workshops based on the